EZH2 mutations are frequent and represent an early event in follicular lymphoma - Bödör, Csaba (American Society of Hematology, 2013)
Gain of function mutations in the H3K27 methyltransferase EZH2 represent a promising therapeutic target in germinal center lymphomas. In this study, we assessed the frequency and distribution of EZH2 mutations in a large cohort of patients with follicular lymphoma (FL) (n = 366) and performed a longitudinal analysis of mutation during the disease progression from FL to transformed FL (tFL) (n = 33). Mutations were detected at 3 recurrent mutation hot spots (Y646, A682, and A692) in 27% of FL cases with variant allele frequencies (VAF) ranging from 2% to 61%. By comparing VAF of EZH2 with other mutation targets (CREBBP, MLL2, TNFRSF14, and MEF2B), we were able to distinguish patients harboring clonal EZH2 mutation from rarer cases with subclonal mutations. Overall, the high incidence of EZH2 mutations in FL and their stability during disease progression makes FL an appropriate disease to evaluate EZH2 targeted therapy.